Penurunan Fungsi Ventrikel Kanan pada Subjek dengan Obstructive Sleep Apnea - Rony M Santoso; Anna U Rahajoe; Ismoyo Sunu (Jurnal Kardiologi Indonesia, 2013)
An analytical design study on the systolic right ventricle (RV) functionwas done in Obstructive Sleep Apnea (OSA) patients who underwentpolisomnography procedure and compare it with normal subject. Theassessment of the RV function was performed using the Speckle trackingechocardiography method. Other RV function parameters such as TAPSE,Tissue Doppler Imaging (TDI), dan Myocardial Performance Index (MPI)were also measured.The results showed RV dysfunction in OSA patients compared with normalsubject, the decrease of RV function was significantly different betweenthe two groups. Factors that contributed to RV dysfunction in OSA patientswere higher Apnea-Hypopnea Index (AHI) and Nocturnal OxygenDesaturation.